Teachers of Arabic Proficiency in Rational Conflict Resolution Methods and Its Relationship to Tolerance Values among Secondary School Students: A Field Study in Ashirqat District - Shehab, Thabet Jaddoa (Journal of Tikrit University for Humanities, 2024)
The study aimed to explore a relationship between the extent to which Arabic language teachers possess methods for resolving conflicts in a reasonable manner and the values of tolerance among secondary school students in the Shirqat district. The research community consisted of a group of Arabic teachers who teach the secondary stage in the Shirqat district, numbering (70) male and female teachers. Also, it consists of some secondary school students in Al-Sharqat District, who numbered (11,834) male and female students. The research sample consisted of (372) male and female students, including (220) male and (182) female secondary school students whose numbers were calculated through an equation Stephen Thompson, the study reached several results, perhaps the most prominent of which is that the relationship between the degree of methods for resolving conflicts in a reasonable manner and the values of tolerance is positive, meaning that the greater the degree to which teachers possess methods for resolving conflicts by peaceful means, the greater the values of tolerance among their students. The study also concluded with a set of recommendations, including developing training programs for teachers, as it is recommended to design intensive training programs for Arabic teachers that focus on teaching effective methods for resolving conflicts in a reasonable manner. It is also possible to include educational content on promoting the values of tolerance and developing effective communication skills, and also activating the role of families and society by involving parents and individuals. The community supports Arabic teachers in developing conflict resolution skills and promoting the values of tolerance among students.